Creative orientation of formation of musical-aesthetic orientations of the future teachers in cognitive activity - Ponomarova, O.M. (Pedagogy of Higher and Secondary Education, 2006)
The article deals with some problems of aestenc and musical orientations in the process of students' creative activity.